Plasma adenosine and neurally mediated syncope: ready for clinical use. Issue 6 (25th May 2020) - Brignole, Michele; Groppelli, Antonella; Brambilla, Roberto; Caldara, Gianluca L; Torresani, Erminio; Parati, Gianfranco; Solari, Diana; Ungar, Andrea; Rafanelli, Martina; Deharo, Jean Claude; Marlinge, Marion; Chefrour, Mohamed; et al.
Abstract: Either central or peripheral baroreceptor reflex abnormalities and/or alterations in neurohumoral mechanisms play a pivotal role in the genesis of neurally mediated syncope. Thus, improving our knowledge of the biochemical mechanisms underlying specific forms of neurally mediated syncope (more properly termed 'neurohumoral syncope') might allow the development of new therapies that are effective in this specific subgroup. A low-adenosine phenotype of neurohumoral syncope has recently been identified. Patients who suffer syncope without prodromes and have a normal heart display a purinergic profile which is the opposite of that observed in vasovagal syncope patients and is characterized by very low-adenosine plasma level values, low expression of A2A receptors and the predominance of the TC variant in the single nucleotide c.1364 C>T polymorphism of the A2A receptor gene. The typical mechanism of syncope is an idiopathic paroxysmal atrioventricular block or sinus bradycardia, most often followed by sinus arrest. Since patients with low plasma adenosine levels are highly susceptible to endogenous adenosine, chronic treatment of these patients with theophylline, a non-selective adenosine receptor antagonist, is expected to prevent syncopal recurrences. This hypothesis is supported by results from series of cases and from observational controlled studies.